PENGARUH KUALITAS PELAYANAN PUBLIK DAN DISIPLIN KERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT(Studi Pelayanan Haji Di Kantor Kementerian Agama Kabupaten Kaur): (Studi Pelayanan Haji Di Kantor Kementerian Agama Kabupaten Kaur) - Budiman; Budiman Sakti; Rahimandani; Elza Risanti (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
This research aims to examine the influence of the quality of public services and employee work discipline on public satisfaction in Hajj services at the Ministry of Religion, Kaur Regency. The method used in this research is a sampling method of 50 respondents in the community who will register themselves as prospective pilgrims at the Ministry of Religion of Kaur Regency. There are three problem formulations and hypotheses proposed to be proven through partial tests (t-test) and simultaneous tests (F-test). To analyze the magnitude of each coefficient of public service quality and employee work discipline on the satisfaction of people who receive Hajj services, they are analyzed using a multiple linear regression model. The research results are based on respondents' responses to the indicators used in the research on the variable quality of public services "Very Good, employee work discipline "Good" and satisfaction of people who received Hajj services also received a response of "Good". The results of hypothesis testing using the t-test found a public service quality variable where t-hit = 4.320) > t-table = 1.6679) and p value (sig.α=0.00) < 0.05, on the employee work discipline variable t-hit = 8.946 > t-table) = 1.6679) and p value (sig.α = 0.00) < 0.005. The two hypotheses can be partially concluded that there is a positive and significant influence on the quality of public services and employee work discipline on public satisfaction with Hajj services at the Ministry of Religion, Kaur Regency. The results of this research are supported by simultaneous tests with the F-count test = 73.621 ≥ F-table = 3.20) and p value (Sig.α = 0.00) < 0.05, the conclusion is that the quality of public service and work discipline factors employees simultaneously have an influence on community satisfaction with Hajj services at the Ministry of Religion, Kaur Regency.